Network Pharmacology-Guided Development of a Novel Integrative Regimen to Prevent Acute Graft-vs.-Host Disease - Lyu, Ming; Zhou, Zhengcan; Wang, Xiaoming; Lv, Hong; Wang, Mei; Pan, Guixiang; Wang, Yuefei; Fan, Guanwei; Gao, Xiumei; Feng, Yuxin; Zhu, Yan (Frontiers in Pharmacology, 2018)
Lapses in the graft-versus-host disease (GVHD) prophylaxis and side effects of current standard care following allogeneic hematopoietic stem cell transplantation (allo-HSCT) call for novel regimens. Traditional approaches targeting T cells showed limited success in preventing acute GVHD (aGVHD). System medicine showed promising results treating complex diseases such as sepsis and multi-organ dysfunction syndrome (MODS). Adapting established network pharmacology analysis methods, we aimed to develop novel integrative regimens to prevent aGVHD. Our network pharmacology analysis predicted that Xuebijing injection (XBJ) targets a series of key node proteins in aGVHD network. It also unveiled that Salviae miltiorrhizae (Danshen), an herb in Xuebijing formula, which prevented acute GVHD in rats, shares five out of six key GVHD node proteins targeted by XBJ. Interestingly, network pharmacology analysis indicated Xuebijing may share multiple aGVHD targets with Cyclosporin A (CsA), a first-line drug for preventing acute GVHD in the clinic. Based on current information, we hypothesized that combination of XBJ and CsA may yield superior results in aGVHD prevention than either drug alone. We performed in vitro and in vivo assays to validate the predictions by the network pharmacology analysis. In vitro assays revealed XBJ prevented platelet aggregation and NF-κB nuclear translocation in macrophages. XBJ also promoted angiogenesis in tube-formation assay. Importantly, the combination of CsA and XBJ was effective in rescuing mice subjected to lethal GVHD. XBJ contributed to the rescue through preventing NF-κB nuclear translocation, attenuating inflammation and maintaining viability of macrophages. Overall, network pharmacology is a powerful tool to develop novel integrative regimens. Combination of XBJ and CsA may shed light on preventing aGVHD.